UPAYA PENGOBATAN DAN PERAWATAN MANDIRI OLEH KELUARGA DENGAN ANAK INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Mebi " Rania; Yufitriana " Amir; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Acute Respiratory Infection (ARI) is the most frequent illness in children, so we need maximum effort to minimize, one of them likes self medication and self care intervention by family. The purpose of this research is to identify self medication and self care by family with child acute respiratory infection (ARI) at Public Health Center of Harapan Raya in the year of 2017. The research design is descriptive study by using consecutive sampling technique. Samples of this research were 142 families. The research instrument was a questionnaire with sub variables self medication and self care that has been tested good validity ang reliability. This research used univariate analysis to know the distribution of frequencies self medication and self care. The result of this research showed from 142 families majority has self medication and self care that less adequate as many as 138 families (97,2%) 129 familis (90,8%). The result of this research showed that adequate self medication the most from 10 questions about medication of reducing temperature that was given when child was fever, and the medication was paracetamol and ibuprofen that was 135 families (95,1%). The result about self care that was adequate the most of 6 questions was about given orange fruit when child was sick as many as 116 families (81,7%). The conclusion from this research, the adequate effort may be that was many communication, information and education from health workers. This research recommended that family has active participation for do the self medication and self care until we can reached the traditional and complementary program. Keywords: Child acute respiratory infection (ARI), families, self medication and self care